DIGITAL OIL FIELD – FROM DATA TO REAL-TIME DECISION MAKING – SMART WORKING FOR OPERATIONS EFFICIENCY - Mohammad Rostami Dehka; Iulian Nistor (Romanian Journal of Petroleum & Gas Technology, 2021)
Digital Oil Field (DOF) project in OMV Petrom aims to remotely monitor, troubleshoot and optimize operations and maintenance data and activities in a modern manner, and to foster value creation through increased integrated and reliable performance data availability to skilled professionals in order to facilitate the right decisions. DOF Project started as a pilot in an oil field, covering a large area of automated wells and facilities. The pilot field is operating around 400 wells equipped with PCP (progressive cavity pump) and more than 70% automated facilities consisting of: 14 MPSs (Meter Point Skids), 2 PMANs (Production Manifolds) and 1 OMS (Oil Metering Station), all connected to SCADA systems